1997
DOI: 10.1111/j.1365-2753.1997.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient, physician and presentational influences on clinical decision making for breast cancer: results from a factorial experiment*

Abstract: This study examines the influence of six patient characteristics (age, race, socioeconomic status, comorbidities, mobility and presentational style) and two physician characteristics (medical specialty and years of clinical experience) on physicians' clinical decision making behaviour in the evaluation treatment of an unknown and known breast cancer. Physicians' variability and certainty associated with diagnostic and treatment behaviour were also examined. Separate analyses explored the influence of these non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 137 publications
0
52
0
Order By: Relevance
“…25 Controlled videotape-based experiments designed to isolate the effects of physician characteristics have found that the age of the clinician affected medical decision making. 26,27 We can only hypothesize as to why more recent training was not associated with reduced LOS among hospitalists. It is likely that the magnitude of benefit due to the potential advantages of onsite location and experience with inpatient diagnoses and systems outweighs and obscures any variance in LOS attributable to being more recently trained.…”
Section: Discussionmentioning
confidence: 99%
“…25 Controlled videotape-based experiments designed to isolate the effects of physician characteristics have found that the age of the clinician affected medical decision making. 26,27 We can only hypothesize as to why more recent training was not associated with reduced LOS among hospitalists. It is likely that the magnitude of benefit due to the potential advantages of onsite location and experience with inpatient diagnoses and systems outweighs and obscures any variance in LOS attributable to being more recently trained.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, health insurance status is highly associated with cancer-screening participation and the stage of disease at the time of diagnosis (Ayanian, Kohler, Abe, et al 1993;Catalano and Satariano 1998;Lannin, Mathews, Mitchell, et al 1998;Parker, Gebretsadik, Sabogal, et al 1998;Potosky, Breen, Graubard, et al 1998;Eisen, Waterman, Skinner, et al 1999;Lewis and Asch 1999), and also with access to the best available treatments (Greenberg, Chute, Stukel, et al 1988;Hadley, Steinberg, and Feder 1991;Mitchell, Meehan, Kong, et al 1997;McKinlay, Burns, Durante, et al 1997;Bennett, Stinson, Yang, et al 1999). Rate ratios generally range from 1.50 to 2.50, basically indicative of twofold greater access among those with more generous insurance payers.…”
Section: Cancer Carementioning
confidence: 99%
“…1,2 In particular, research indicates that the care a patient receives may be as much a function of who the patient is (age, gender, race= ethnicity, socioeconomic status [SES]), who the provider is (age, gender, specialty), and where the care is delivered (private= public facility, geographic location) as it is of the symptoms actually present. [3][4][5][6][7][8][9][10] A compelling example is coronary heart disease (CHD), the single greatest cause of death for men and women in the United States and Europe. Remarkably, women generally have lower age-adjusted CHD incidence and mortality than men.…”
mentioning
confidence: 99%